If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6X + 13 + 7X = -2 Reorder the terms: 13 + -6X + 7X = -2 Combine like terms: -6X + 7X = 1X 13 + 1X = -2 Solving 13 + 1X = -2 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 1X = -2 + -13 Combine like terms: 13 + -13 = 0 0 + 1X = -2 + -13 1X = -2 + -13 Combine like terms: -2 + -13 = -15 1X = -15 Divide each side by '1'. X = -15 Simplifying X = -15
| -.45(40)+.8X=.3(40+X) | | 2(-10)+5y=10 | | 4w+3w-6w-6w=w+15+2w-31 | | 1-5x=13+x | | 4g^2+2g+3=0 | | 4X+8-3X=3 | | 2y+6=8+3y | | (x-2)(3x+5)= | | -10/x=5/x-10/3 | | x-255=443 | | 46=3u-11 | | 600=2500(X)(4) | | (5x-2)/2x-18 | | 4n-6.4=2(n+1.3) | | (5x-2)/2x-18=0 | | x+255=433 | | 6x^2+7x-2= | | -4r+12=-72 | | 4/840=4/x | | 4/3x-2=16 | | 840/x=3/4 | | 3x-5(-2+3x)=10 | | r^2+69r-216=0 | | 2/7t-10/7t | | x-0.7=8.59 | | 0=-16t+vt+16 | | 11A-13=-7A^2 | | j^2-20j+36=0 | | 0=(x-9)(3x+1) | | 3/840=4/x | | n-3/4=5/12 | | 3m-2(m+7)=m-14 |